PAMAM dendrimers as a carbamazepine delivery system for neurodegenerative diseases: A biophysical and nanotoxicological characterization - Igartúa, Daniela (2018)
Carbamazepine (CBZ) is an antiepileptic drug, which also could be used in the treatment of neurodegenerative diseases, such as the Alzheimer's disease. However, its use has been limited due to its low solubility, inefficient pharmacokinetic profiles, and multiple side effects. PAMAM dendrimers, ethylenediamine core, generation 4.0 (amine terminal groups) and 4.5 (carboxylate terminal groups) (DG4.0 and DG4.5 respectively) are polymers that can increase drug solubility through complexation. Thus, the aim of this work was to obtain and characterize complexes between CBZ and dendrimers. Both DG4.0 and DG4.5 allowed the incorporation of ∼20 molecules of CBZ per dendrimer, into their hydrophobic pockets. DG4.0-CBZ and DG4.5-CBZ complexes were found to be stable for 90 days at 37 °C and resistant to a lyophilization process, presenting controlled drug release. Also, the complexes nanotoxicity was tested ex vivo (human red blood cells), in vitro (N2a cell line), and in vivo (zebrafish). No hemolytic effect was observed in the ex vivo model. As regards in vitro toxicity, the DG4.5-CBZ complexes significantly reduced the toxicity caused by the free drug. Moreover, the DG4.5-CBZ did not cause neurotoxicity or cardiotoxicity in zebrafish larvae. In conclusion, a stable and biocompatible drug delivery system based on the DG4.5 capable of complex the CBZ has been developed. This achievement highlights the advantages of using negatively charged dendrimers for nanomedicine.